Pengaruh Perputaran Piutang, Struktur Modal dan Kepemilikan Manajerial terhadap Nilai Perusahaan - Retno Wulandari; Alya Budiantini (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study examines the effect of accounts receivable turnover, capital structure, and managerial ownership on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period. The research was conducted using a quantitative associative approach with purposive sampling, resulting in 23 companies as the final sample. Secondary data were obtained from published annual reports, and the analysis was performed using multiple linear regression. The findings show that accounts receivable turnover does not have a significant effect on firm value, indicating that the speed of receivable collection is not a determining factor for market valuation within the observed period. Capital structure has a positive and significant effect on firm value, suggesting that the composition of debt and equity plays an important role in shaping investors’ perceptions. Meanwhile, managerial ownership does not significantly influence firm value, which may be related to the relatively low proportion of shares owned by management in the sampled firms. Overall, the three variables have a significant effect on firm value when tested simultaneously. These results highlight the importance of financial structure in determining firm value while suggesting that internal ownership and receivable efficiency alone do not provide strong market signals.